Person-Level Predictors of Agreement Among Weekly, Peak, and End Reports of Positive and Negative Affect: Ego Resilience and Big Five Personality Traits - Chu, Xiatian (Wake Forest University, 2025)
Retrospective evaluations of emotional experiences often diverge from momentary reports. The present study investigated whether personality traits and resilience predict individual differences in peak and end biases when recalling positive and negative affect. Using ecological momentary assessment (EMA) over five weeks with 196 college students, we collected momentary reported and weekly evaluated affect ratings, alongside baseline measures of personality and resilience. Contrary to hypotheses, multilevel models showed that extraversion and neuroticism did not moderate peak bias in retrospective recall of emotions. Resilience was not associated with stronger peak bias in positive affect but was linked to attenuated peak bias in negative affect, suggesting a buffering effect. Additional mediation models revealed that resilience predicted more positive recall of emotions through greater typical positive affect. These findings highlight the nuanced role of person-level factors in shaping individuals’ recall of affective experiences.
Keywords: Emotion; Peak and End Rule; Personality; Recall Bias; Resilience